Monitoring and projecting snow on Hawaii Island. Issue 5 (11th May 2017) - Zhang, Chunxi; Hamilton, Kevin; Wang, Yuqing
Abstract: The highest mountain peaks on Hawaii Island are snow covered for part of almost every year. This snow has aesthetic and recreational value as well as cultural significance for residents and visitors. Thus far there have been almost no systematic observations of snowfall, snow cover, or snow depth in Hawaii. Here we use satellite observations to construct a daily index of Hawaii Island snow cover starting from 2000. The seasonal mean of our index displays large interannual variations that are correlated with the seasonal mean freezing level and frequency of trade wind inversions as determined from nearby balloon soundings. Our snow cover index provides a diagnostic for monitoring climate variability and trends within the extensive area of the globe dominated by the North Pacific trade wind meteorological regime. We have also conducted simulations of the Hawaii climate with a regional atmospheric model. Retrospective simulations for 1990–2015 were run with boundary conditions prescribed from gridded observational analyses. Simulations for the end of 21st century employed boundary conditions based on global climate model projections that included standard scenarios for anticipated anthropogenic climate forcing. The future projections indicate that snowfall will nearly disappear by the end of the current century. Key Points: A new daily snow cover index for Hawaii Island is constructed based on MODIS satellite imagery Seasonal mean snow cover for Hawaii Island is a sensitive indicator of interannual climate variability Model projections indicate that there will be a long‐term trend of reduced snowfall and the near absence of all snow by 2100 Plain Language Summary: This study addresses the issue of monitoring Hawaii snow and projecting its expected long‐term trend over the current century. The motivation is not simply the concern that disappearing snow will affect the quality of experience for residents and visitors, but also the value of snow cover as a sensitive diagnostic of the state of the climate in Hawaii and one that we think can add significantly to the quantitative characterization of global climate change. Our study is of particular interest as we introduce and investigate an integrated diagnostic of the climate state in an otherwise sparsely observed part of the globe within the meteorological "trade wind regime" (TWR). The TWR covers a large portion of the globe where typical conditions feature large‐scale subsidence and widespread stratocumulus clouds at the base of trade wind inversion. The TWR regions play a crucial role in the global climate system, notably through the cooling influence of the extensive low clouds, and modeling the TWR cloud response is a key uncertainty in projecting global warming. By improving our knowledge of climate variability and change within the TWR, our study contributes to the general quest for better understanding and more confident predictions of anthropogenic global warming.